Cultural Paradigms of Knowledge Creation: Exploring Eastern Philosophical Practices and Western Ideological Frameworks - Dr. Zamin Abbas; Mohsin Ehsan Niazi (Dialogue Social Science Review (DSSR), 2025)
Cultural frameworks shape knowledge creation, a foundation of human progress. This article examines the relationship between Eastern philosophical traditions and Western ideological frameworks, categorizing their distinct contributions to knowledge development. Eastern paradigms emphasize intuition, interconnectedness, and holistic approaches, drawing from traditions such as Confucianism, Taoism, and Vedanta. In contrast, Western frameworks prioritize analysis, individualism, and empirical evidence, rooted in Enlightenment principles and scientific empiricism. Despite extensive research in this area, key gaps remain. These include the limited exploration of diverse Eastern traditions, insufficient empirical validation of their practical applications, and the lack of integrated hybrid models that synthesize both paradigms. To address these gaps, this study employs a comparative epistemological analysis of foundational texts, contextualized case studies in organizational and educational settings, and the development of a conceptual synthesis framework. This framework seeks to merge Eastern and Western knowledge paradigms to tackle modern global challenges such as sustainability, digital transformation, and cross-cultural collaboration. By bridging these perspectives, this research offers innovative pathways for advancing knowledge creation and application in an increasingly interconnected world.